Enhanced neutron diagnostics data acquisition system based on a time digitizer and transient recorder hybrid module - Pereira, R. C. (2006)
This paper proposes a new transient recorder (TR)-time digitizer (TD) hybrid system to be used to pull out higher performance of presently used techniques for measuring the collimated flux and the spectrum of the neutron emission from fusion plasmas of either deuterium or deuterium-tritium, as well as to apply to new neutron measuring techniques, with demanding specific requirements in plasma physics. This system is presented as a modular design, allowing up to four 200 MHz, 12 b acquisition channels to operate in an interleaved way, achieving 800 MHz. The module includes a XILINX FPGA and an ADC front-end along with a large memory storage capacity and unique TD capabilities (two channels with 36 ps resolution). The FPGA is able to perform real-time data validation as well as some processing algorithms to obtain physical parameters and module calibration. Processed data will be transferred to a control unit by a gigabit optical link. The system will be able to support multiple front-end modules operating synchronously.